Determination of side products of stilbene synthesis by gas chromatography and chromato-mass spectrometry - Averin, V.A.; Aruslanova, R.I.; Budakovsky, S.V.; Volkov, V.L.; Vashchenko, V.V.; Knyazeva, I.V. (Functional Materials, 2008)
The impurity composition of trans-stilbene obtained by synthesis and purified by various techniques has been studied using combination of gas chromatography and chromato-mass-spectrometry. The results obtained made it possible to identify the impurities to be limited and to improve the technology of scintillation grade trans-stilbene.